Strict Liability in Environmental Dispute Responsibility Before and After the Enabling of Omnibus Law - Zahranissa Putri Faizal (Fakultas Hukum Universitas Lampung, 2021)
With the limitation of the principle of fault-based liability, which is not effective in the implementation of the responsibility for activities with high risk, Law No. 23 of 1997 concerning Environmental Management and Law no. 32 of 2009 concerning Environmental Protection and Management which adheres to the principle of absolute responsibility or strict liability. The regulation regarding the principle of strict liability is clarified in Article 88 of Law no. 32 of 2009 (UU PLH). However, with the passing of the Omnibus Law, which changed Article 88 of Law no. 32 of 2009 becomes article 88 of the Omnibus Law, which eliminates the principle of strict liability. This writing uses a normative approach, a statutory approach. The data analysis used is a qualitative analysis. The elimination of strict liability in resolving environmental disputes is considered a shift, which in the provisions of Article 88 of the Job Creation Law seems to provide an opportunity for corporations to pollute the environment without firm accountability. The government seems to protect the sustainability of a corporation more than the interests of the community. The type of research used in this study is using normative legal research methods using a statutory approach and literature study.